2011
DOI: 10.1016/j.jdent.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Association between caries location and restorative material treatment provided

Abstract: Objectives This cross-sectional study by the Northwest PRECEDENT practitioners correlated the location of caries diagnosed in the past 12 months with treatment provided. Methods An oral health survey was conducted on up to 20 patients per practice for 101 practices in the Northwest PRECEDENT network. A total of 1943 eligible patients were randomly assessed for the location of and treatment provided for caries lesions diagnosed within the past 12 months. Regression analysis using Generalized Estimating Equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…This implicates that the choice of restoration material used, was dependent upon the time period and not on cavity design unlike other studies (Lubisich et al, 2011). The two operators in this practice had a conservative approach towards caries treatment.…”
Section: Discussionmentioning
confidence: 84%
“…This implicates that the choice of restoration material used, was dependent upon the time period and not on cavity design unlike other studies (Lubisich et al, 2011). The two operators in this practice had a conservative approach towards caries treatment.…”
Section: Discussionmentioning
confidence: 84%
“…molar or premolar, maxillary or mandibular, paths and areas of occlusal forces and patient's preference have not taken into consideration while conducting the study 8 as dentist and practice properties (gender of practitioner, years since graduation and type of practice), patient properties (sex, race, age and dental insurance status); and caries characteristics (tooth location and surface, preoperative and postoperative lesion depth) are associated with the type of restorative material used 19,23 . So, in this study, results are based entirely on the dentists' individual perception and experience and represent their perspective on different fi lling materials for different tooth cavities in permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the location of caries, oral hygiene, dietary habits and salivary condition. 43 Moreover, immature superficial enamel and dentine structures 44 and dietary habits increase the caries risk for young subjects resulting in more active carious lesions. 32 In the present study, it was demonstrated that measuring the pH of the carious lesion might serve as an indicator for real-time caries activity diagnosis, and facilitate follow up on non-surgical treatments and monitoring of arrested lesions where a recurrence is probable.…”
Section: Discussionmentioning
confidence: 99%